EVALUASI PELAKSANAAN PROGRAM BANTUAN PERBAIKAN RUMAH UNTUK RUMAH TANGGA MISKIN (RTM) DI KOTA DENPASAR - Hermawati, Wiwik; Sutarja, I N.; Nadiasa, Mayun (JURNAL SPEKTRAN; Vol. 3, No. 2, Juli 2015, 2015)
The endeavor of Denpasar City Government in establish the wellbeing of its people especially the underprivileged households is conducting a house renovation aid program in order to accomplish the essential privileges of livable and healthy housing. With numerous problems during the development program execution, therefore, this study is carried out to evaluate the program implementation to determine the program effectiveness index and its relationship between the program effectiveness and the increase of the wellbeing of underprivileged households. The primary data are composed from survey feedbacks of sequence of questions in a questioner. While, the secondary data were collected from Office of Spatial Planning and Housing of the City of Denpasar and other related agencies. The methods used in data collection consist of interviews and questionnaires.  Out of 30 questions in the questioner, all were affirmed valid and reliable. The analytical tool utilize in the study were descriptive analysis, effectiveness analysis in term  of input variables, output variables, outcome variables and impact variables which modify Dantes' formula; and Chi Square analysis to distinguish the relationship between program effectiveness and program's impact to wellbeing improvement. Of the five Dante's categories of effectiveness index, the analysis of the feedbacks of 68 respondents which distributed in four districts in the City of Denpasar are presented in this study. The total score value of program implementation effectiveness, indicated by X, X = 4581, within the range 3400 ? X ? 4760. This index value showed that the implementation of the house renovation for underprivileged households aid program is classified to be less effective. The value of Chi Square of the study is greater than its critical value (47.33 > 13.277). It is indicating that there is a significant relationship between program effectiveness and the program impact to the people wellbeing improvement. It is suggested that when the program and its impact is to be continued, the effectiveness variables need to be optimized and so the managements improvements in order to increase the wellbeing of the underprivileged households.
Keywords: Evaluation, Effectiveness, Underprivileged Households, House Renovation Aid Program